湿式双离合自动变速器起步控制策略研究 - 迟宝山; 华玉龙; 孙伟; 刘国强 (Jixie chuandong)
Based on the characteristics of dual-clutch transmission,the single clutch dynamic model during starting process is built,and single clutch control strategy is established.Taking a Skoda car as the experimental object in the case of study,the clutch control strategy is validated in improving the starting quality of dual clutch transmission vehicle efficiently.